Efektifitas Media Komik terhadap Pengetahuan Manajemen Kebersihan Menstruasi: Effectiveness of Comic Media on Menstrual Hygiene Management Knowledge - Nadila, Roja; Tampubolon, Masrina Munawarah; Utami, Sri (Poltekes Kemenkes Tanjungpinang, 2024)
Knowledge of menstrual hygiene management is influential in maintaining and caring for reproductive organs. Adolescent knowledge can be improved through health education with media like comics. The study was conducted to determine the effectiveness of comic media on knowledge of menstrual hygiene management. The research used a quasi-experiment method through a pretest and posttest design with a non-equivalent control design. The research sample was 64 high school students selected by proportional random sampling. The analyses applied were Wilcoxon and Mann-Whitney statistical tests. The Wilcoxon test results compared the mean knowledge before and after providing health education or education using comic media with a p-value = 0.000 < α (0.05). In the Mann-Whitney test value conducted on the experimental group and the control group, the p-value = 0.002 was obtained. There was a difference in the average knowledge in the group given the intervention compared to the group without the intervention. Providing education or health education through the use of comics in the form of media is considered effective in improving knowledge of menstrual hygiene management.